Determinants of Decarbonisation in the Transformation of the Energy Sector: The Case of Poland - Magdalena Wójcik-Jurkiewicz; Marzena Czarnecka; Grzegorz Kinelski; Beata Sadowska; Katarzyna Bilińska-Reformat (Energies, 2021)
This paper aims to identify the determinants of the decarbonisation processes in Poland within the scope of energy transformation. The purpose of the study is to identify how the public perceives decarbonisation determinants in order to develop a sustainable energy strategy for Poland. The transition of the energy market to low-carbon technology is a policy challenge. Governments must implement policies that are environmentally friendly, cost-effective, but, most of all, socially acceptable. Social acceptance risk plays a significant role in Poland, influencing the decarbonisation process. In Poland’s case, the coal share is decreasing, but it is still the most important fuel for electricity production. This process of decarbonisation is a fundamental influence on the transformation of the energy sector in Poland. The social perception of solutions that can be applied was examined. The Polish natural environment is poisoned. Poles suffer from diseases related to the burning of coal for energy production. Societal awareness, how people perceive the government’s actions, and what they expect in this regard is crucial.